Perspektive imagologije - Smolej, Tone (Primerjalna književnost, 2001)
Imagological perspectives. - The aim of this paper is to discuss some problems concerning imagology and provide insights into them on the basis ofexamples taken from French literature.
Keywords: francoska književnost; imagologija; literarna zgodovina; primerjalna književnost